Crisis Management and an Ethic of Care: The Case of Northern Rock Bank - Linsley, Philip M.; Slack, Richard E. (2013)
Different ethical frameworks have been proposed as appropriate for integrating into crisis management strategies. This study examines an ethic of care approach to crisis management analysing the case of Northern Rock bank which was at the centre of the recent financial crisis in the UK. The development and maintenance of relationships is fundamental to an ethic of care approach and the research recognises this by examining the bank–stakeholder relationship both before and after the crisis. Considerable anger was directed at the bank post-crisis and, subsequently, the management team resigned. An important contention is that because an ethic of care approach had not been followed external parties judged that management should have foreseen the crisis and the harm caused was deemed intentional, even though predicting the crisis would have been difficult and it is improbable any harm was intended. Additionally, this negative reaction was heightened due to three facets of Northern Rock’s history: (i) its previous existence as a building society, (ii) the ‘local’ nature of the bank and (iii) the creation of The Northern Rock Foundation. These historical factors caused local stakeholders to presume a ‘caring’ relationship between themselves, and the bank had continued to exist post-demutualisation. The events of the crisis compelled stakeholders to re-appraise this presumption, amplifying the post-crisis anger.
Keywords: Crisis; Intention; Foresight; ethic of care; Crisis Management; Bank